Design of array antenna for wireless communication - Satrusallya, Sarmistha; Narayan Mohanty, Mihir (International Journal of Engineering and Technology, 2018)
As antenna plays a major role in communication, it paves a way towards wireless communication. Use of antenna array in wireless commu-nication for different application is the focused area of research in current years. In this paper, an attempt is taken to design an antenna array with rectangular parasitic patches around the modified rectangular patch at the centre. The gap is maintained within the central patch. Further to achieve better performance, optimization of the parasitic elements is considered. Using popular genetic algorithm the patch dimensions are optimized. The performance in terms of bandwidth, gain and return loss found better than the un optimized design. The result shows the efficiency and observed.Â Â